Kinetic spectrophotometric determination of Para-amino benzoic acid in pharmaceutical preparation by diazotization-coupling reaction - Alsalamy, Zainab (University of Thi-Qar Journal of Science, 2025)
Modest and delicate kinetic approaches are industrialized used for the resolve of Para-amino benzoic acid in unadulterated form and in pharmaceutical measures. The process is based on diazotization   of benzoic acid and coupling with 1,2,3-Trihydroxybenzene in natural medium to form a brown-reddish water-soluble azo dye, that has a maximum absorption at 446nm. We used the constant time method (15 minutes) with an initial rate of speed as a reference. We also scrutinized the reaction kinetics and determined the most favorable conditions for studying the reaction kinetics in 15 minutes. Drug kinetics were calculated from the linear drug kinetics using a calibration curve, with the initial velocity rate method and constant time method both having the concentration range (1*10-4-1*10-5 M). Pharmaceutical preparations utilized effortless methods to determine (PABA) using workable techniques.